Transformation of gaseous 2-bromophenol on clay mineral dust and the potential health effect. (July 2019) - Wang, Yi; Peng, Anping; Chen, Zeyou; Jin, Xin; Gu, Cheng
Abstract: Iron-bearing clays are ubiquitously distributed as mineral dusts in the atmosphere. Bromophenols were reported as the major products from thermal decomposition of the widely used brominated flame retardants (BFRs). However, little information is available for the reactivity of iron associated with mineral dusts to interact with the atmospheric bromophenols and the subsequent toxic effects. Herein, three common clay minerals (montmorillonite, illite and kaolinite) were used to simulate mineral dusts, and the reactions with gaseous 2-bromophenol were systematically investigated under environmentally relevant atmospheric conditions. Our results demonstrate that structural Fe(III) in montmorillonite and Fe(III) from iron oxide in illite mediated the dimerization of 2-bromophenol to form hydroxylated polybrominated biphenyl and hydroxylated polybrominated diphenyl ether. The surface reaction is favored to occur at moisture environment, since water molecules formed complex with 2-bromophenol and the reaction intermediates via hydrogen bond to significantly lower the reaction energy and promote the dimerization reaction. More importantly, the formed dioxin-like products on clay mineral dust increased the toxicity of the particles to A549 lung cell by decreasing cell survival and damaging cellular membrane and proteins. The results of this study indicate that not only mineral dust itself but also the associated surface reaction should be fully considered to accurately evaluate the toxic effect of mineral dust on human health. Graphical abstract: Image 1 Highlights: Iron-bearing clays are major component of mineral dust which is the omnipresent constituent of earth's atmosphere. The iron-bearing clays mediated the dimerization of gaseous 2-bromophenol to form HO-PBB and HO-PBDE. The reaction is highly favored at high relative humidity, while suppressed at low relative humidity. The toxicity of the clay particles to human lung cell A549 increased after the heterogeneous reaction.